1999
DOI: 10.1091/mbc.10.11.3607
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of G2 Arrest in Response to Overexpression of p53

Abstract: Overexpression of p53 causes G2 arrest, attributable in part to the loss of CDC2 activity. Transcription of cdc2 and cyclin B1, determined using reporter constructs driven by the two promoters, was suppressed in response to the induction of p53. Suppression requires the regions Ϫ287 to Ϫ123 of the cyclin B1 promoter and Ϫ104 to Ϫ74 of the cdc2 promoter. p53 did not affect the inhibitory phosphorylations of CDC2 at threonine 14 or tyrosine 15 or the activity of the cyclin-dependent kinase that activates CDC2 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
149
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(162 citation statements)
references
References 71 publications
11
149
0
1
Order By: Relevance
“…17 A possible mechanism that could explain this observation is that cytoplasmic accumulation of cyclin B1 in tumor cells favors the premature entry into mitosis by overriding a p53-mediated G2/M checkpoint, thus promoting uncontrolled cellular proliferation and disease progression. 41 Conclusively, the association of altered protein levels and an altered subcellular expression pattern with disease progression support a substantial role of cyclin B1 in the carcinogenesis of RCC. Moreover, it has been described that tumors retaining cyclin B1 in the cytoplasm tend to be resistant to DNA damage-induced apoptosis.…”
Section: Discussionmentioning
confidence: 87%
“…17 A possible mechanism that could explain this observation is that cytoplasmic accumulation of cyclin B1 in tumor cells favors the premature entry into mitosis by overriding a p53-mediated G2/M checkpoint, thus promoting uncontrolled cellular proliferation and disease progression. 41 Conclusively, the association of altered protein levels and an altered subcellular expression pattern with disease progression support a substantial role of cyclin B1 in the carcinogenesis of RCC. Moreover, it has been described that tumors retaining cyclin B1 in the cytoplasm tend to be resistant to DNA damage-induced apoptosis.…”
Section: Discussionmentioning
confidence: 87%
“…Increasing evidence indicates that deregulation and overexpression of cyclin B1 is involved in neoplastic transformation in many tumor types (Soria et al, 2000;Hassan et al, 2002;Yuan et al, 2006). Constitutive activation of cyclin B1 and associated cdc2 kinase can override the G2 DNA damage checkpoint, which leads to an accumulation of genomic defect found in malignant tumors (Kao et al, 1997;Taylor et al, 1999;Park et al, 2000). Recent reports that forced RNAi-mediated reduction of cyclin B1-induced continuous apoptosis in tumor cells (Yuan et al, 2004(Yuan et al, , 2006 are in accordance with this observation.…”
Section: Discussionmentioning
confidence: 99%
“…35,37,38 Well-known p53-responsive genes include CDC2, CCNB1, and TOP2a. [39][40][41] Despite the transcription factors E2F and NF-Y being enriched in both groups, cell cycle-dependent element (CDE) was significantly enriched in the target group and upstream stimulating factor (USF) was enriched in the non-target group. Previous analyses of CDC2 and CCNB1 promoters suggested that p53 interacted with NF-Y to mediate trans-repression, 42 although a subsequent study suggested that p53 trans-repressed through interaction with SP1.…”
Section: Discussionmentioning
confidence: 99%